Observations on natural enemies of Lobesia botrana (Den. & Schiff.) (Lepidoptera Tortricidae) in Venetian vineyards (Bollettino di zoologia agraria e bachicoltura, 2024)
During the years 1989-1993 a study on the presence and the role of the natural enemies of L. botrana Den. & Schiff. in two vineyards of North-Eastern Italy was carried out. More than 30 species of parasitoids and numerous species of predators feeding on juvenile stages were collected. The most widespread species among the parasitoids were Dicaelotus inflexus Thomson, Tranosemella prerogator L., Dibrachys affinis Masi, Itoplectis alternans (Gravenhorst), Pimpla spuria Gravenhorst, Campoplex capitator Aubert, Colpoclypeus florus (Walker), Elasmus steffani Viggiani and Phytomyptera nigrina (Meigen). The predatory activity of insects and arachnids has been noticed particularly on overwintering stages. Even the pathogens (fungi, viruses and microsporidia) seem to be important in controlling the population density of L. botrana. Mortality rates due to the complex of natural enemies are variable in different vineyards, generations and years. The influence of pest management on the presence and activity of the beneficial organisms has been evaluated.
Keywords: Lobesia botrana; predators; parasitoids; pathogens